Modern seasonality in Lake Challa (Kenya/Tanzania) and its sedimentary documentation in recent lake sediments - Christian Wolff; Iris Kristen-Jenny; Georg Schettler; Birgit Plessen; Hanno Meyer; Peter Dulski; Rudolf Naumann; Achim Brauer; Dirk Verschuren; Gerald H. Haug (Limnology and Oceanography, 2014)
From November 2006 to January 2010, a sediment trap that was cleared monthly was deployed in Lake Challa, a deep stratified freshwater lake on the eastern slope of Mt. Kilimanjaro in southern Kenya. Geochemical data from sediment trap samples were compared with a broad range of limnological and meteorological parameters to characterize the effect of single parameters on productivity and sedimentation processes in the crater basin. During the southern hemisphere summer (November—March), when the water temperature is high and the lake is biologically productive (nondiatom algae), calcite predominated in the sediment trap samples. During the “long rain” season (March—May) a small amount of organic matter and lithogenic material caused by rainfall appeared. This was followed by the cool and windy months of the southern hemisphere winter (June—October) when diatoms were the main component, indicating a diatom bloom initiated by improvement of nutrient availability related to upwelling processes. The sediment trap data support the hypothesis that the light—dark lamination couplets, which are abundant in Lake Challa cores, reflect seasonal delivery to the sediments of diatom‐rich particulates during the windy months and diatom‐poor material during the wet season. However, interannual and spatial variability in upwelling and productivity patterns, as well as El Niño—Southern Oscillation (ENSO)‐related rainfall and drought cycles, exert a strong influence on the magnitude and geochemical composition of particle export to the hypolimnion of Lake Challa.